The Impact of Modern Technologies and Methods on the Management of Key Logistics Activities - Macura, Nikola; Pavličević, Marija; Marić, Tijana; Anđelić, Milosav; Popović, Nikica (Anali Ekonomskog fakulteta u Subotici, 2026)
Purpose: This paper examines the impact of modern technologies and methods on the management of key logistics activities, with a particular focus on warehousing and transportation. The aim is to assess how innovative logistics solutions contribute to improving the speed, efficiency, safety, and sustainability of logistics operations. Methodology: The study is based on a review of relevant academic and professional literature, supported by case studies of leading global companies, including Amazon, Alibaba, JD.com, Walmart, DHL, UPS, IKEA, and Alphabet. The analysis covers modern warehousing and transportation technologies, including robotics, automation, artificial intelligence, drones, and Hyperloop solutions. Findings: The findings indicate that the adoption of modern logistics technologies significantly improves operational efficiency, reduces logistics costs, accelerates order processing and delivery, enhances warehouse space utilization, and contributes to more sustainable logistics systems. At the same time, successful implementation requires substantial initial investments, workforce upskilling, and organizational adaptation. Originality/value: The paper provides an integrated overview of the most important contemporary logistics technologies and methods by examining their practical implementation in leading global companies, highlighting their advantages, limitations, and implications for the future development of logistics systems. Practical implications: The findings may assist logistics managers and decision-makers in selecting and implementing modern logistics solutions to improve competitiveness, service quality, and operational efficiency. Limitations: The paper is based on a literature review and case study analysis rather than empirical research. Consequently, the conclusions represent a synthesis of existing knowledge and provide a foundation for future empirical studies.